Effects of Knowledge Hiding in Dual Teaching Methods on Students’ Performance—Evidence From Physical Education Department Students - Xu, Qingxiang; Jiesen, Yin (Frontiers in Psychology, 2022)
With the post-pandemic situation, digitalization has revolutionized physical teaching into online teaching and became a common practice. The engagement of students has been an essential part of their good academic performance which can be ensured with the active participation of the students that is a real challenge for teachers. However, sometimes in online and physical teaching, teachers are also involved in rationalized knowledge hiding, which leads to the disengagement of the students and ultimately affects their academic performance. The population of the present study is the students of universities in China belonging to different fields of study. The sample size for this study is 246. The data is obtained through the questionnaire surveys. The existing study has assessed the role of teachers’ rationalized knowledge hiding behaviors in the disengagement of students and their lessened grades. It has been found that rationalized knowledge hiding in online teaching does not affect students performance, however, makes students disengage from their studies. Interestingly, the rationalized knowledge hiding in physical teaching has negatively affected the students' performance. Furthermore, the mediating role of student disengagement has been found significant in this study. Organizations, especially universities, can ensure the maximum knowledge sharing by connecting in the positive reinforcement behaviours to stimulate the instructors. This study will be supportive for the principal body of the universities in ensuring the greatest quality outcome of the teaching classes, workshops, and seminars conducted either physically or online so no instructor involves in rationalized knowledge hiding.